Variable frequency ultrasonic pest repeller / Khairul Azwan Mohamed Idris and Megat Mohd Lokman Megat Aminuddin - Mohamed Idris, Khairul Azwan; Megat Aminuddin, Megat Mohd Lokman (2001)
In today’s world, the term digital has become part of our everyday vocabulary because of dramatic way that digital techniques has become so widely used in almost all area of life. This project known as VARIABLE FREQUENCY ULTRASONIC PEST REPELLER We can on or off our switch at home or others It is suitable for every one and it easy to use. For the time being, insect can be found in every house. So we decided to create this project to prevent the insect.